János Kornai's Contributions to Economic Analysis - Assar Lindbeck (Research Institute of Industrial Economics (IFN), 2007)
The publication of János Kornais memoirs, By Force of Thought, provides an excellent opportunity to remind ourselves of Kornais great contributions to economic research. This paper discusses both his basic research strategy and some of his main research results. Kornai has usually dealt with great, system-oriented issues, and he has been more inspired by real-world observations than by scholarly work by others. The paper also emphasizes that Kornais two most celebrated characterizations of real world socialist economies shortage economies and production units with soft budget constraints are analytically closely connected. Kornai also, in his more recent works, regards the centralized political system during communism as the basic explanation for the centralized nature of the economic system in these countries.
Keywords: B24; B31; L10; P20; 330; Socialism; Soft Budget Constraints; Shortage Economy; Economic Centralization; Sozialismus; Zentrale Wirtschaftsplanung; Budgetrestriktion; Übergangswirtschaft; Dogmengeschichte